2021
DOI: 10.3389/fphar.2021.634344
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and Non-Alcoholic Steatohepatitis

Abstract: Background: The excessive consumption of free sugars is mainly responsible for the high prevalence of obesity and metabolic syndrome in industrialized countries. More and more studies indicate that fructose is involved in the pathophysiology and also in the degree of disease of non-alcoholic fatty liver disease (NAFLD). In epidemiologic studies, energy-adjusted higher fructose consumption correlates with NAFLD in overweight adults. In addition to glucose, fructose, as an equivalent component of conventional ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 60 publications
0
34
1
8
Order By: Relevance
“…Free sugars, such as sucrose or fructose, are consumed in quantities two to three times the recommended intake, which is less than 10% of energy intake, and cause a fatty liver due to overweight and obesity. Especially high intake of fructose, which is metabolized mostly in the liver, affects hepatic energy metabolism with modulation of the liver gene expression involved in the regulation of different metabolic pathways which lead to hepatic steatosis, with fructose being an inducer of and a substrate for hepatic lipogenesis [ 12 ]. A high intake of fructose can explain some cases of “lean” NAFLD [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free sugars, such as sucrose or fructose, are consumed in quantities two to three times the recommended intake, which is less than 10% of energy intake, and cause a fatty liver due to overweight and obesity. Especially high intake of fructose, which is metabolized mostly in the liver, affects hepatic energy metabolism with modulation of the liver gene expression involved in the regulation of different metabolic pathways which lead to hepatic steatosis, with fructose being an inducer of and a substrate for hepatic lipogenesis [ 12 ]. A high intake of fructose can explain some cases of “lean” NAFLD [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Especially high intake of fructose, which is metabolized mostly in the liver, affects hepatic energy metabolism with modulation of the liver gene expression involved in the regulation of different metabolic pathways which lead to hepatic steatosis, with fructose being an inducer of and a substrate for hepatic lipogenesis [ 12 ]. A high intake of fructose can explain some cases of “lean” NAFLD [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of reversal of liver fibrosis with weight loss, so that modification of diet, physical activity, and weight loss are advocated for patients with NAFLD [142]. Regarding diet, a clinical study reported that a carbohydrate-restricted diet may be more effective in the reduction of hepatic steatosis than a low fat-diet, probably, due to a reduced content of fructose [143]. Excessive use of fructose has been demonstrated to increase plasma triglycerides and de novo lipogenesis in the liver [144].…”
Section: Nafld and Lifestyle Interventionsmentioning
confidence: 99%
“…Steatosis occurs in hepatocytes due to two main mechanisms [ 22 ] - increased accumulation which is due to the overflow of free fatty acids (FFAs) from adipocyte tissue (which contributes to 60% of the stored fat), increased de novo lipogenesis (25%) and FFA from the diet (15%-20%) and reduced output which is due to reduced FFA oxidation and reduced secretion of lipids. De novo lipogenesis is particularly affected by the consumption of fructose in “sugary” drinks [ 23 ].…”
Section: Reviewmentioning
confidence: 99%